NAMPT and NAPRT, Key Enzymes in NAD Salvage Synthesis Pathway, Are of Negative Prognostic Value in Colorectal Cancer - Li, Xiao-qin; Lei, Jing; Mao, Lin-hong; Wang, Qing-liang; Xu, Feng; Ran, Tao; Zhou, Zhi-hang; He, Song (Frontiers in Oncology, 2019)
Nicotinamide adenine dinucleotide (NAD) is a profoundly important cofactor in redox reactions. Nicotinamide phosphoribosyltransferase (NAMPT) and nicotinate phosphoribosyltransferase (NAPRT) are key enzymes for NAD salvage biosynthesis pathway, which reciprocally synthesize NAD to supply the main source of NAD biosythesis. However, the prognostic value of NAMPT and NAPRT in colorectal cancer (CRC) remains largely unknown. Our present study detected NAMPT and NAPRT protein expression in cancer and adjacent tissues from 261 CRC using immunohistochemical staining. We found that high expression of NAMPT or NAPRT was associated with vascular invasion, invasion depth and advanced TNM stage in CRC. High expression of NAMPT or NAPRT predicts short overall survival and disease-free survival time in CRC patients, which were further confirmed by public datasets. Furthermore, positive correlation between expression of NAMPT and NAPRT was revealed in CRC tissues and cell lines. NAPRThigh/NAMPThigh patients tended to have the shortest survival time. Using the TCGA RNA-sequencing data, we showed that gene amplification, mutation, and methylation of NAPRT are more common than NAMPT. On the other hand, NAMPT gene might be targeted by more miRNAs. Finally, genes that are correlated with NAPRT or NAMPT are enriched in different pathways. In conclusion, we found that high expression of NAMPT or NAPRT predicts poor prognosis of CRC patients, but the regulatory mechanism might be distinct from each other.